Risks, Ethics, and Airport Security - O'Malley, Pat (Canadian journal of criminology and criminal justice, 2006)
A key distinction needs to be made between formal and informal risk profiling. It is usually assumed that formal risk profiling, based on statistical data, provides an optimal means of prediction and thus of detecting high-risk individuals or situations. However, it must be recognized that formal profiles are based extensively on informal profiles - those built upon the experience and working cultures of security-related officials. Formal profiles are thus prone to the same errors and tend to produce self-fulfilling prophecies, resulting in both errors of fact and discriminatory consequences for false-positive cases. All profiles, however, are fraught with problems, perhaps the most obvious and significant being that the targets of interdiction readily become aware of them and modify their operations to incorporate activities and/or individuals that do not fit existing profiles. Consequently, totally risk-based security, ironically, may become less effective than alternatives such as randomly assigned focused interdictions. (English) [ABSTRACT FROM AUTHOR]